1990
DOI: 10.1111/j.1600-079x.1990.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin Agonists and Antagonists on Reproduction and Body Weight in the Siberian Hamster

Abstract: This study examined whether melatonin-induced inhibition of testicular weight and body weight in vivo could be antagonized by luzindole, a competitive melatonin receptor antagonist, or methysergide, a competitive serotonin receptor antagonist. Adult male Siberian hamsters were exposed to a long photoperiod (16L:8D) and given daily injections of drugs 3 h before lights off for 7 weeks. Hamsters treated with melatonin (0.375 mg/kg) exhibited testicular regression and loss of body weight. These effects were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The melatonin effect was not blunted by the melatonin receptor antagonist luzindole. In this regard, Duncan et al [1990] found that concomitant administration of luzindole did not inhibit the antigonadal effects of melatonin. Several different factors may have contributed to the ineffectiveness of luzindole in the present study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The melatonin effect was not blunted by the melatonin receptor antagonist luzindole. In this regard, Duncan et al [1990] found that concomitant administration of luzindole did not inhibit the antigonadal effects of melatonin. Several different factors may have contributed to the ineffectiveness of luzindole in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…This biphasic effect is due to the activation of Gi and compound to be very low. In the Siberian hamster, the affinity of melatonin for its receptors is much greater than that of luzindole [Duncan et al, 1990]. This may also help to explain why luzindole does not antagonize the effect of melatonin in the rat frontoparietal cortex.…”
Section: Discussionmentioning
confidence: 95%
“…High doses (30 mg/kg) of luzindole, an MT1/MT2 antagonist/inverse agonist, were without effect on hamster reproductive responses to photoperiod or MEL (11), suggesting that disruption of MEL signaling at MT1/MT2 receptors is compatible with normal photoperiodic responses. In contrast, late afternoon injections of MEL elicit changes in ependymal cell layer expression of type II and type III iodothyronine deiodinase mRNA (Dio2 and Dio3, respectively) in wild-type mice but fail to do so in mice with targeted disruption of the MT1 receptor (12).…”
mentioning
confidence: 89%
“…Melatonin is known for its modulatory role in gonadal development and reproduction in rodents (Duncan 1990;Reiter 1987), birds (Ralph 1970) as well as fish (Garg 1988). Its direct action on the gonads was also implicated in a few reports (Ayre 1992;Wang 1992).…”
Section: Discussionmentioning
confidence: 99%